The Kinematics of Breasts Implanted With a Reduced Mass Implant: A Pilot Study. (24th October 2019) - Norris, Michelle; Jones, Melissa; Mills, Chris; Blackmore, Tim; Inglefield, Chris; Wakefield-Scurr, Joanna
Abstract: Background: Breast implants may increase breast skin tension and interact with surrounding tissues to alter breast position and motion during dynamic activity. Reducing implant mass and changing implant location (submuscular/subglandular) may also affect breast kinematics and the subsequent loads on breast structures. Objectives: The aim of this pilot study was to describe the kinematics of breasts augmented with reduced-mass implants during standing, walking, and running, compared with natural breasts, and to provide insight into how implant location (submuscular/subglandular) alters breast kinematics. Methods: Two breast augmentation participants (12–15 months postsurgery: 32AA presurgery, anatomical submuscular 255 cc B-Lite reduced-mass implant; 32A presurgery, anatomical subglandular 285 cc B-Lite reduced-mass implant) and 2 natural-breasted participants of similar breast size and anthropometrics were recruited. Nipple and torso positional data were recorded with electromagnetic sensors during standing, walking, and running. Nipple kinematics relative to the torso were calculated. Results: The B-Lite participants both displayed greater nipple projection and elevation during standing and a 50% reduction in nipple acceleration during walking, when compared with their natural counterparts. During running, the B-Lite subglandular participant displayed decreased nipple kinematics compared with her natural counterpart and lower nipple kinematics compared with the B-Lite submuscular participant during walking and running. Conclusions: A combination of implant location (subglandular) and reduced mass minimized nipple kinematics during running. Reducing nipple kinematics during dynamic activity may decrease the loading on breast structures, helping to decrease ptosis and increase the longevity of procedure outcomes. Level of Evidence: 4: